Analisis Learning Obstacles Siswa Pada Materi Pecahan Kelas IV Sekolah Dasar - Siti Khazanatu Rohmah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The purpose of this research to analyze errors of students answer to get a conception of learning obstacles in the fraction material in 4th grade of elementary school. This analysis is important as a basis to prepare teaching materials and to predict of student responses and how to anticipate. This research used the qualitative method. The research subjects were 32 student of 5th grade elementary school who had studied fractions in grade IV in Tasikmalaya Regency. Based on the results of analysis of test and interview data, there are several barriers on student learning. First, didactical obstacles were identified from mistake doing the test problems which is caused by how students studied and materials which used by students such as fraction material that did not clearly define how fractions was and emphasize knowledge procedures, then students do not study fractions through the partitioning process, somewhere partitioning will make learning easier. Second, epistemological obstacles as a result from errors in the processing of questions caused by the limited context of knowledge possessed by students. For example, the definition of fractions which are part of the whole, students are limited to that context without paying attention at the parts as equal/more or less. In addition, procedures of student understanding for example fraction simplification, fraction sequencing, and subtraction and addition of fractions are limited to certain questions. When the questions are different than usual, there are students who didn’t understand the purpose of the problem.